Pengaruh Kemampuan Komunikasi dan Literasi Digital terhadap Kinerja Guru di Pondok Pesantren Modern Al-Fatimah Bojonegoro - Ansachul Balaya; Bambang Sigit Widodo; Meini Sondang; Amrozi Khamidi; Mochamad Nursalim (LP. Ma'arif Janggan Magetan, 2024)
Teachers' communication skills and digital literacy influence how they deliver education and maintain learning quality. This research examines the influence of communication skills and digital literacy on teacher performance at Al-Fatimah Modern Islamic Boarding School in Bojonegoro. The method used in this research is quantitative method to determine the relationship between the studied variables, where teachers' communication ability serves as the first independent variable (X1), digital literacy as the second independent variable (X2), and teacher performance as the dependent variable (Y). This research used primary data with questionnaires as the data collection technique administered to 102 respondents. Based on correlation tests, multiple correlation tests, simple regression analysis, and multiple regression analysis, the research results showed that communication skills and digital literacy have a significant influence on teacher performance at Al-Fatimah Modern Islamic Boarding School in Bojonegoro.